Peningkatan Minat Baca dan Literasi Digital melalui Pojok Baca Interaktif Ramah Anak - Habiburrahman Habiburrahman; Riya Fatmawati (ABDI HUMANIORA: Jurnal Pengabdian Masyarakat Bidang Humaniora, 2020)
The Community Partnership Program aims to build an interactive and child-friendly reading corner at the Mukarramah Orphanage in Nan Sabaris District, Padang Pariaman Regency. The targets to be achieved in this program are: 1) Providing literacy facilities for children of orphanages in the form of child-friendly reading corners, 2) Increasing the reading interest of orphanage children by providing interesting and varied collections, 3) Providing search soft skills training digital information for children of the Mukarramah orphanage. The implementation of this activity begins with designing and building in such a way a corner of the Mukarramah Orphanage by attracting and paying attention to child-friendly elements. Procurement of furniture consisting of bookshelves that are easily accessible to children, procurement of bean bags so that children relax reading, procurement of interesting and interactive collections that suit the needs of children, and procurement of tablet computers with kids mode facilities that can be used online and offline as a means for children to learn and play, as well as providing soft skills training in the form of digital information tracking to teenagers in orphanages. For the evaluation of the achievement of objectives will begin by looking at the extent to which interactive and child-friendly reading corners are built to attract children to come and utilize collections, and measure the ability of adolescent children at the Mukarramah Orphanage to effectively track needed information.